A kukorica fuzáriumos szártőkorhadásával szembeni rezisztenciavizsgálat módszertani értékelése provokációs kísérletekben - Kovács, Blanka; Pécs, Márton; Gergely, László; Szőke, Csaba (GEORGIKON FOR AGRICULTURE, 2022)
Fusarium Stalk Rot (FSR) caused by Fusarium spp., especially F. graminearum and F. verticillioides is the No. 1. disease in Hungary. Therefore resistance testing is obligatory in the process of variety registration. In 2015 and 2019 disease-provocation trials were conducted in two locations (Röjtökmuzsaj and Martonvásár) using different methods, soil-inoculation and toothpick-inoculation. Three maize genotypes carrying different level of field resistance were inoculated with Hungarian isolates of F. graminearum and F. verticillioides. Based on our results, both inoculation techniques are suitable for resistance screening, but we prefer soilinoculation as a non-invasive way of testing. Off the isolates, F. graminearum has shown higher pathogenicity in the toothpick trial. As for soil-inoculation, F. verticillioides has caused greater infection on the mid-susceptible genotype, than F. graminearum. In the practice of state registration, it is advisable to use both Fusarium species in resistance tests because they are prevalent in Hungary.
Keywords: maize; Fusarium Stalk Rot; disease-provocation trial; inoculation methods; variety registration